SNAI2 and TWIST1 in lymph node progression in early stages of NSCLC patients. (29th May 2018) - Emprou, Camille; Le Van Quyen, Pauline; Jégu, Jérémie; Prim, Nathalie; Weingertner, Noëlle; Guérin, Eric; Pencreach, Erwan; Legrain, Michèle; Voegeli, Anne‐Claire; Leduc, Charlotte; Mennecier, Bertrand; Falcoz, Pierre‐Emmanuel; et al.
Abstract: Lymph node metastasis is an important prognosis factor in non‐small cell lung cancer (NSCLC) patients. The aim of this study was to investigate the role of epithelial to mesenchymal transition (EMT) in lymph node progression in the early stages of NSCLC. We studied a retrospective cohort of 160 consecutive surgically treated NSCLC patients with available frozen tumor samples for expression of EMT markers ( CDH1, CTNNB1, CDH2, and VIMENTIN ), inducers ( TGFB1, c‐MET, and CAIX), and transcription factors (EMT‐TF: SNAI1, SNAI2, ZEB1, TWIST1, and TWIST2 ). Partial EMT was more frequent in N1‐2 (N+) vs N0 patients ( P  <   .01). TGFB1 ( P  =   .02) as well as SNAI2 ( P  <   .01) and TWIST1 ( P  =   .04) were the most differentially expressed genes in N+ tumors. In this group, ZEB1 was correlated with all EMT inducers and other EMT‐TFs were overexpressed depending on the inducers. CAIX was an independent prognostic factor for overall survival (IC 95% HR: 1.10‐5.14, P  =   .03). Partial EMT is involved in lymph node progression of NSCLC patients and depends on the TGFβ pathway. EMT‐TFs are differentially expressed depending on EMT inducers. CAIX might be a relevant prognostic marker in early stage NSCLC. Abstract : The aim of the present retrospective study was to simultaneously describe some EMT markers, effectors, and inducers in a retrospective cohort of early stage NSCLC by comparing N0 and N+. We found that partial EMT is involved in lymph node progression of NSCLC patients and depends on the TGFβ pathway. EMT‐TFs are differentially expressed depending on EMT inducers. CAIX might be a relevant prognostic marker in early stage NSCLC.